2013
DOI: 10.1002/jbmr.2143
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Trabecular Bone Benefits of Mechanical Loading Are Maintained Long Term in Mice Independent of Ovariectomy

Abstract: Skeletal loading enhances cortical and trabecular bone properties. How long these benefits last after loading cessation remains an unresolved, clinically relevant question. This study investigated long-term maintenance of loading-induced cortical and trabecular bone benefits in female C57BL/6 mice and the influence of a surgically induced menopause on the maintenance. Sixteen-week-old animals had their right tibia extrinsically loaded 3 days/week for 4 weeks using the mouse tibial axial compression loading mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Subsequent bone growth is more obviously related to changes in physiologic demand or the mechanical loading environment (Frost & Jee, ; Martin et al ; Carter & Beaupre, ; Currey, ). BV/TV, in particular, has been shown to be highly responsive to dynamic loading (Goldstein et al ; Van Rietbergen et al ; Warden et al ; Prot et al ). Ryan et al () describe divergent ontogenetic patterns in the humerus and femur, in which the latter demonstrates significantly higher BV/TV after about 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent bone growth is more obviously related to changes in physiologic demand or the mechanical loading environment (Frost & Jee, ; Martin et al ; Carter & Beaupre, ; Currey, ). BV/TV, in particular, has been shown to be highly responsive to dynamic loading (Goldstein et al ; Van Rietbergen et al ; Warden et al ; Prot et al ). Ryan et al () describe divergent ontogenetic patterns in the humerus and femur, in which the latter demonstrates significantly higher BV/TV after about 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mechanical loading during growth preferentially deposits new bone on the outer periosteal surface to increase bone size [66, 67], whereas the loss of bone mass during aging primarily occurs via intracortical bone loss adjacent to the endocortical surface [68]. The discordant bone surface effects of loading and its cessation enables the bone size benefits of loading when young to persist and have lasting benefits on bone strength, as the latter is most influenced by the distance of its material from the neutral axis (i.e., bone size) [64, 65]. …”
Section: Muscle Forces On Bone During Locomotionmentioning
confidence: 99%
“…We demonstrated that mechanical loading during a period of rapid skeletal growth conferred lifelong benefits in bone size and strength in rodent models (18,19). To explore whether the same phenomenon occurs in humans, the current study used a uniquely controlled cross-sectional study design that compared differences in humeral…”
mentioning
confidence: 99%